Thermoelectric Energy Harvesting System (TEHs) At Asphalt Pavement With A Subterranean Cooling Method - Khamil, Khairun Nisa; Md Yusop, Azdiana; Mohd Sabri, Mohd Faizul (Taylor & Francis Group, LLC, 2020)
In this study, a thermoelectric energy harvesting system (TEHs) that utilized the heat from the surface of asphalt pavement is proposed with the aim to investigate the effects of the heat conduction using different shape structures in the subterranean level. The design model consisted of asphalt base holder to hold the asphalt, top plate for heating, and bottom plate for cooling. The top plate is exposed on the asphalt surface to harvest heat from sunlight, and the bottom plate is submerged into the pavement. The bottom plate is then connected to the cooling element, to take advantage of subterranean cooling to achieve a high-temperature difference between the top and bottom plate of the TEHs. In the past studies, subterranean cooling proved to maintain the underground temperature, but there is no assurance of high-temperature difference. Simulation and experimental investigation were conducted on how the shape structure affects the heat conduction in the subterranean level for two types of cooling elements, which is a cylindrical rod and flat bar. Both simulation and experimental results demonstrate that the cylindrical rod has yielded a higher temperature difference compared to the flat bar. Higher output voltage was generated for the case of the cylindrical rod due to more effective cooling, which resulted in larger temperature differences. Contradicted to previous studies, the fieldtesting has proved the system with asphalt has indeed influenced the temperature distribution into the system with a 24.39% increase of temperature difference in comparison to the system without the asphalt. Hence, the introduction of subterranean cooling and asphalt pavement heating has proved to improve the performance of TEHs, which makes it possible for utilization as an energy harvester